Endodontic retreatment of a mesotaurodontic mandibular first molar with C-shaped configuration in a patient with multiple taurodonts: A case report and review of literature - Mina Davaji; Sahar Karimpour (Wolters Kluwer Medknow Publications, 2024)
Taurodontism is a dental anomaly characterized by an apical displacement of the pulp chamber floor, resulting in a large pulp chamber with short roots. It can be associated with certain syndromes and abnormalities, although it is common to occur as an isolated characteristic. This anomaly can occur along with other root canal system anomalies such as C-type configuration. The aim of this report is to present the successful endodontic management of a C-shaped mesotaurodontic mandibular molar and review the literature available on this matter. A 23-year-old Persian female was referred by her dental surgeon to complete the root canal treatment of her right mandibular first molar (#46). Clinical examination showed a temporized cavity with no response to pulpoperiapical tests or visible pocket depth while an elongated root trunk with slight periodontal ligament widening, incomplete obturation of the root canal system, and periapical radiolucency was evident on the intraoral radiograph. Cone-beam computed tomography (CBCT) revealed a taurodontic and type III C-shaped root canal configuration. With a diagnosis of previous treatment and asymptomatic apical periodontitis, the patient was scheduled for root canal retreatment. The same anomaly was discovered in other molar teeth on the panoramic radiograph taken before the primary treatment of tooth #46. At a 2-month follow-up session, the tooth was found asymptomatic clinically and radiographically. The past publications about the management of nonsyndromic taurodontic molars were also reviewed. The review of 29 similar articles showed that preoperative CBCT, magnification with illumination, along with active irrigation are helpful items in managing such cases.